2015
DOI: 10.5935/abc.20150039
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Correlates to Functional Aerobic Impairment in Hemodialysis Patients

Abstract: BackgroundAutonomic dysfunction (AD) is highly prevalent in hemodialysis (HD) patients and has been implicated in their increased risk of cardiovascular mortality.ObjectiveTo correlate heart rate variability (HRV) during exercise treadmill test (ETT) with the values obtained when measuring functional aerobic impairment (FAI) in HD patients and controls.MethodsCross-sectional study involving HD patients and a control group. Clinical examination, blood sampling, transthoracic echocardiogram, 24-hour Holter, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Unregulated ANS is present in hemodialysis patients because it directly targets several vital organs, and can even lead to death in cardiac compromise 8,9. One of the main causes of ANS imbalance in renal patients is related to cardiovascular problems 8,9,12. HRV is greatly impaired in its normal functioning when it is related to cardiac arrhythmias associated with these patients 8,9,12.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unregulated ANS is present in hemodialysis patients because it directly targets several vital organs, and can even lead to death in cardiac compromise 8,9. One of the main causes of ANS imbalance in renal patients is related to cardiovascular problems 8,9,12. HRV is greatly impaired in its normal functioning when it is related to cardiac arrhythmias associated with these patients 8,9,12.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced HRV is an increased risk of death in several populations, but its prognostic value in patients with hemodialysis remains uncertain 9. Literature has investigated the existing relationship between HRV in patients carriers of CKD who undergo hemodialysis, and observed that high mortality is related to an erroneous functioning of cardiac autonomic regulation 12…”
Section: Introductionmentioning
confidence: 99%
“…[7,8] Dysfunction of the ANS has been related to cardiovascular events in patients with CRD. [79] Several studies have shown the relationship between HRV reduction and the development of complex arrhythmias in these patients. [79] Generally, in the most advanced stage of this pathology, there are changes that are noticed in almost all systems of the body: nervous, cardiovascular, respiratory, musculoskeletal, immunologic, and endocrine/metabolic.…”
Section: Discussionmentioning
confidence: 99%
“…[79] Generally, in the most advanced stage of this pathology, there are changes that are noticed in almost all systems of the body: nervous, cardiovascular, respiratory, musculoskeletal, immunologic, and endocrine/metabolic. [79]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation